Rice farmers' preferences for seed quality, packaging, and source: A study from northern Bangladesh - Sarkar, Md. Abdur Rouf; Habib, Muhammad Ashraful; Sarker, Mou Rani; Rahman, Md. Mahbubur; Alam, Sultanul; Manik, Md. Nazmul Islam; Nayak, Swati; Bhandari, Humnath (2024)
The use of quality seeds is crucial to improve rice yield, food security, and farmers’ livelihoods. The large informal seed system, limited access to quality seeds, and low seed replacement rate challenge increasing rice yield. Despite robust government initiatives to support the seed system, progress has been slow. Besides, the need for farmers’ behavioural change, enhanced coordination, and communication at the local level has not received adequate attention. We investigate rice farmers’ preferences for quality seed, packet sizes, types, and sources, and assess the impact of utilizing good quality seed. We collected quantitative data from 1196 rice farmers in northern Bangladesh in 2019. To identify major factors influencing farmers’ preferences regarding quality seed, packet sizes, packet types, and seed sources, we employed ordered logit and multinomial logit models. Additionally, we used the propensity score matching procedure to assess the impact of good quality and formal seed sources on the rice yield. The findings revealed that farmers strongly prefer using seeds from formal sources despite limited accessibility. Of the total farmers, 34% use public source seeds, 33% use private source seeds, and the rest rely on their own saved seeds. The use of good quality seeds increased rice yields from the base yield by 0.07–0.28 t/ha. We found about a 48% gap in accessing good-quality seeds, indicating significant potential for scaling up the seed systems. Farmers using formal seed sources yielded 0.03–0.15 t/ha more than informal seed users. Farmers strongly prefer 5 kg packets due to their cost-effectiveness, easy storage, and handling convenience. Additionally, farmers prefer polycoated jute sacks for their versatility, multi-purpose applications, and resistance to pests. The econometric model results showed that farmers’ preferences were significantly influenced by gender, farm type, crop yield, seed price, market distance, various stakeholders’ advice, and seed supply systems’ constraints. The government should implement policies and programs to strengthen a well-connected seed network in rural areas, promoting inclusivity, and enhancing rice productivity. Besides, farmers’ needs and preferences should be considered in designing and implementing seed-related initiatives to foster sustainable agricultural development.